Comparative evaluation of body mass index among school children with and without Bruxism of age group of 6-12 years in Kanchipuram district: A cross-sectional study - Lokesh Siva; Vivek Krishnamoorthy; K Sugumaran Durai; S Syed Shaheed Ahamed; S Rajakumari; N C Catherine (Wolters Kluwer Medknow Publications, 2021)
Aim: To evaluate and compare the body mass index (BMI) of school-going children with bruxism and without bruxism of age between 6 and 12 years. Settings and Design: To find the correlation between BMI and oral habit bruxism among school children and compare with those children without bruxism. Materials and Methods: A total of 6122 children were screened from 28 government and 12 private schools, in which 1854 (30.28%) had various types of oral habits. Among this 280 children had the stressful habit bruxism. The BMI of those children was calculated by measuring the height and weight. The values were compared with the BMI of same number of students of same age group, who does not have any oral habits, with the WHO standard. The values were calculated and tabulated for the statistical analysis, using the SPSS software version 19 (IBM company) with the P < 0.05 as statistically significant. Results: Its shows that children with bruxism has high BMI range, was in the order of overweight > Normal > Underweight, but the BMI of children without any habit was in the order of normal > Underweight > Overweight. On comparison, it was statistically significant. Conclusion: The habit bruxism had a positive correlation with the BMI of children. The children are more stressed from both indoor and outdoor. Hence, kindly educate all the parents, teachers, and public to identify the cause for the habit, because each oral habit is strongly deep rooted with some emotional and/or psychological problem and to make the children stress free in future.